2014
DOI: 10.1016/j.jmb.2013.09.007
|View full text |Cite
|
Sign up to set email alerts
|

The Plant Host Can Affect the Encapsidation of Brome Mosaic Virus (BMV) RNA: BMV Virions Are Surprisingly Heterogeneous

Abstract: Brome mosaic virus (BMV) packages its genomic and subgenomic RNAs into three separate viral particles. BMV purified from barley, wheat and tobacco have distinct relative abundances of the encapsidated RNAs. We seek to identify the basis for the host-dependent differences in viral RNA encapsidation. Sequencing of the viral RNAs revealed recombination events in the 3′ untranslated region of RNA1 of BMV purified from barley and wheat, but not from tobacco. However, the relative amounts of the BMV RNAs that accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 66 publications
(75 reference statements)
1
38
0
Order By: Relevance
“…We found that the SGF appears to be dependent on the host species, suggesting the involvement of host factors that differ among host species play a role in its regulation. In agreement with our findings, Ni et al also found that the relative abundances of encapsidated and total RNA segments of BMV were also dependent on the host species 34 . Indeed, when the ratios of the three segments were followed during the progression of infection in two monocot hosts, they converge into stable SGF total (1:2:3 for barley and 1:2:2 for wheat).…”
Section: Discussionsupporting
confidence: 93%
“…We found that the SGF appears to be dependent on the host species, suggesting the involvement of host factors that differ among host species play a role in its regulation. In agreement with our findings, Ni et al also found that the relative abundances of encapsidated and total RNA segments of BMV were also dependent on the host species 34 . Indeed, when the ratios of the three segments were followed during the progression of infection in two monocot hosts, they converge into stable SGF total (1:2:3 for barley and 1:2:2 for wheat).…”
Section: Discussionsupporting
confidence: 93%
“…Cryo-EM analysis of the BMV virions suggests that phosphorylation affects capsid-RNA interactions. We used a modified CLIP-seq assay to examine the RNA sequences that contact the BMV capsid as a function of CIP treatment (5,39). The nucleotides in the BMV RNA bound to the capsid were enumerated by determination of the number of sequence reads that contained the nucleotide.…”
Section: Resultsmentioning
confidence: 99%
“…The CP is translated from subgenomic RNA4. In a typical infection, RNA4 is coencapsidated with RNA3 in a 1:1 ratio (4), although the host species can influence the encapsidation of the viral RNAs (5).…”
mentioning
confidence: 99%
“…High-throughput DNA sequencing was performed using the Illumina MiSeq system. CLIP-Seq was performed as described previously (17,18). Analyses of MiSeq reads were performed using the Galaxy User Interface.…”
Section: Methodsmentioning
confidence: 99%
“…A protocol that was previously used to examine the interactions between viral proteins with RNA in cells was adapted (17,18) (Fig. 4A).…”
Section: Hnrnp K Can Bind Mir-122 In Cells-mentioning
confidence: 99%